Contribution Of Gravimetry To The Hydrogeological Recognition Of The Area Of Wadi Righ –ouargla - Melouah, O.; Zeddouri, A. (University of Eloued جامعة الوادي, 2017)
Gravimetry is a geophysical methods often used in oil exploration and mining research but rarely in the hydrogeological field, the aim of this work is to exploit the gravimetric data to develop a structural model of the region of Oued Righ - Ouargla has less than 1,000 m depth and perform a litho-stratigraphic modeling of subsurface formations to assess the ability of a karst formation of the terminal complex water table (Eocene Senonian). Multiple filtrations and signal processing techniques for gravimetric datas were operated such as the Euler Déconvolution, the analytical signal and the horizontal gradient. The results were used to evaluate the potential of karstification in the area and to model the phenomenon; the subsurface structural mapping has also led to the relationship between the well productivity and network of faults and fractures.
Articale in Journal of fundamental and Applied Sciences Vol. 09, N. 01
Keywords: Euler deconvolution, analytic signal, faults, karst.